MOVIMENTO VERTICAL DO FÓSFORO PROVENIENTE DO SUPERFOSFATO TRIPLO EM SOLOS DE TEXTURAS CONTRASTANTES - ROSSI, Ana Carolina Marinho; LOPES, Fernando de Souza; KUSANO, Daniel Makoto; ALVES CORRÊA, Marli Aparecida de Oliveira; CAMACHO, Marcos Antonio (ANAIS DO ENIC, 2018)
-